Women’s Religious Maturity in the Perspective of Ḥadīth and Psychology - Fauzi Saleh; Abd Wahid (El-Sunan: Journal of Hadith and Religious Studies, 2026)
Abstract This study aims to examine women’s religious maturity in acts of worship through the analysis of two Prophetic hadiths concerning ritual purification (ghusl) and women’s access to mosques. The first hadith, narrated by ʿĀʾishah and recorded in Sunan Abī Dāwūd and Jāmiʿ al-Tirmidhī, addresses the obligation of ghusl based on the presence of physical evidence rather than subjective experience, and concludes with the statement: “Indeed, women are counterparts of men.” This formulation reflects not only normative equality but also recognition of women’s religious maturity, as they are treated as fully accountable individuals in fulfilling ritual obligations. The second hadith, reported by ʿAbdullāh ibn ʿUmar and preserved in Ṣaḥīḥ Muslim and Ṣaḥīḥ al-Bukhārī, affirms that women should not be prevented from attending mosques. This narration further strengthens the notion of women’s maturity in religious life by acknowledging their independent intention and participation in communal worship, while prohibiting unjust restrictions imposed upon them. Using a contextual (asbāb al-wurūd) and hermeneutical approach, this study finds that both hadiths articulate a coherent prophetic paradigm emphasizing clarity, inclusivity, and facilitation. The findings demonstrate that women are recognized as mature moral agents (mukallafāt), whose religious responsibilities are grounded in objective criteria and whose participation in both private and public worship is legitimate and protected. This study concludes that a contextual reading of hadith reveals an inclusive vision of Islamic teachings that affirms women’s maturity, dignity, and full religious agency in accordance with the higher objectives of the Sharīʿah. Abstrak Penelitian ini bertujuan untuk mengkaji kedewasaan perempuan dalam beribadah melalui analisis dua hadis Nabi yang berkaitan dengan kewajiban mandi (ghusl) dan akses perempuan ke masjid. Hadis pertama, yang diriwayatkan oleh ʿĀʾishah dan terdapat dalam Sunan Abī Dāwūd serta Jāmiʿ al-Tirmidhī, menjelaskan kewajiban mandi berdasarkan indikator fisik, bukan pengalaman subjektif, serta ditutup dengan pernyataan: “Sesungguhnya perempuan adalah saudara kandung laki-laki.” Pernyataan ini tidak hanya menunjukkan kesetaraan normatif, tetapi juga menegaskan pengakuan terhadap kedewasaan perempuan sebagai subjek hukum yang bertanggung jawab penuh dalam pelaksanaan ibadah. Hadis kedua, yang diriwayatkan oleh ʿAbdullāh ibn ʿUmar dan terdapat dalam Ṣaḥīḥ Muslim serta Ṣaḥīḥ al-Bukhārī, menegaskan bahwa perempuan tidak boleh dicegah untuk pergi ke masjid. Hadis ini semakin menguatkan konsep kedewasaan perempuan dalam kehidupan beragama, karena mengakui niat serta partisipasi mandiri mereka dalam ibadah kolektif, sekaligus melarang pembatasan yang tidak beralasan. Dengan menggunakan pendekatan asbāb al-wurūd dan hermeneutika, penelitian ini menemukan bahwa kedua hadis tersebut mencerminkan paradigma kenabian yang menekankan kejelasan, inklusivitas, dan kemudahan. Hasil kajian menunjukkan bahwa perempuan diposisikan sebagai subjek moral yang dewasa (mukallafāt), dengan tanggung jawab ibadah yang didasarkan pada indikator objektif serta memiliki hak untuk berpartisipasi dalam ruang keagamaan publik. Penelitian ini menyimpulkan bahwa pembacaan hadis secara kontekstual mengungkap visi Islam yang inklusif, yang menegaskan kedewasaan, martabat, dan agensi keagamaan perempuan secara utuh, sejalan dengan tujuan utama syariat.